Management of Teacher Performance Improvement in Islamic Boarding Schools - Rasyidin, Rasyidin; Suwandi, Suwandi; Hasibuan, Tarikh Al Hafizh (Universitas Negeri Malang, 2022)
The general purpose of this study is to describe the management of teacher performance improvement. The specific objectives are to describe: 1) planning for improving teacher performance, 2) managing teacher performance improvement, 3) monitoring and evaluating teacher performance improvement management and 4) problems found in managing teacher performance improvement. This research method is descriptive qualitative and data collection techniques are interviews, observations, and documentation. The research subjects were principals and teachers. The results showed that the planning, monitoring and evaluation of the management of improving teacher performance were effective. However, based on the implementation of the management of improving teacher performance, several problems were found, namely external problems and internal problems.